Climate Smart Agriculture? Assessing the Adaptation Implications in Zambia. (5th March 2015) - Arslan, Aslihan; McCarthy, Nancy; Lipper, Leslie; Asfaw, Solomon; Cattaneo, Andrea; Kokwe, Misael
Abstract We examine a set of potentially climate smart agricultural practices, including reduced tillage, crop rotation and legume intercropping, combined with the use of improved seeds and inorganic fertiliser, for their effects on maize yields in Zambia. We use panel data from the Rural Incomes and Livelihoods Surveys merged with a novel set of climatic variables based on geo‐referenced historical rainfall and temperature data to explore the changing effects of these practices with climatic conditions. We estimate the impacts on maize yields, and also on the exhibition of very low yields and yield shortfalls from average levels, as indicators of resilience, while controlling for household characteristics. We find that minimum soil disturbance and crop rotation have no significant impact on these yield outcomes, but that legume intercropping significantly increases yields and reduces the probability of low yields even under critical weather stress during the growing season. We also find that the average positive impacts of modern input use (seeds and fertilisers) are significantly conditioned by climatic variables. Timely access to fertiliser emerges as one of the most robust determinants of yields and their resilience. These results have policy implications for targeted interventions to improve the productivity and the resilience of smallholder agriculture in Zambia in the face of climate change.